Analisis Proses Penyelesaian Klaim Asuransi Kendaraan Bermotor pada PT Asuransi Askrida Syariah Cabang Medan - Gita Kurnia Sari Sembiring; Yusrizal Yusrizal (Al-Kharaj : Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2023)
The purpose of writing this article is to find out how the process and mechanism for resolving motor vehicle insurance claims at PT Asuransi Askrida Syariah Medan branch. The writing method used by the author is a literature review. The literature review method is a method used to describe a finding or theory as material for further research that is obtained and used as a reference material or basis for an activity in the preparation of a framework of thought. PT. Askrida Syariah Insurance Medan City Marketing Office has collaborated with the workshop which is the insurance partner's approval if the participant suffers damage caused by an event in the form of damage and or loss. The claim process also has a short filing time, which is about 5 (five) days after the event experienced by the participant so that claims can be processed immediately. The insured vehicle also has a minimum age of 5 (five) years from the date of issue of the vehicle. This is in accordance with company policy, if the claim document is not fulfilled immediately, the company has the right to postpone or reject the claim. Keywords: Claims, Insurance, Motor Vehicles